Optimization of Ultrasound-Assisted Extraction Parameters from Indigofera Tinctoria L using Response Surface Methodology - Achmad Qodim Syafaatullah; Variyana, Yeni; Ni’matur Rohmah; Iid Mufaidah; Ayu Qurota A’yun (Journal of Research and Technology, 2021)
Nowadays, the natural dyes are commonly used in textile industry. One of them is Indigofera tinctoria L leaves extracting natural dyes that produce blue color and have various potential utilization. However, the extraction time required usually takes a long time using conventional extraction. Thus, some researches reported that ultrasound-assisted extraction can accelerate and increase the extraction yield. The mechanism of ultrasonography is able to assist matrix cell rupture through the ultrasound cavitation. The present research aimed to study and to evaluate the Indigofera tinctoria L dye using ultrasound-assisted extraction. Response surface methodology (RSM) in conjunction with box-behnken design (BBD) was applied to optimize and to analyze the extraction conditions. The independent factors were ratio feed to solvent (0.02-0.1 g/ml), ultrasound temperature (50-60oC), and extraction time (50-90 minutes). Further, feed to solvent ratio was the most significant factor of extraction process in comparison with temperature and extraction time. The optimum extraction conditions were 58oC, 0.02 g/ml, and 50 minutes. The predicted model obtained was 6.025% which close to the actual data (5.75%). Moreover, the extract dye compounds were analyzed by FTIR test and the result was 64.07% for presence of Indigo dye. Therefore, the natural dyes can be alternative and sustainable dye as environmentally friendly